Metabolism in mood disorder across the gut-liver-brain axis - Radford-Smith, DE (2022)
Background and Aims: Depression and nonalcoholic fatty liver disease (NAFLD) are common disorders that share a bidirectional relationship and continue to increase in prevalence. Both maternal depression and obesity during pregnancy increase the risk of neuropsychiatric disease in the offspring. Alterations to systemic immunity and gut microbiota composition are thought to contribute to these relationships, though the precise mechanisms are not known. In rodents, probiotic supplementation has been reported to have anti-inflammatory and antidepressant-like effects, yet it is not clear how modifying the microbiota of obese dams during the perinatal period may affect the behaviour, metabolism, and neuroplasticity gene expression of their offspring. Principally, this thesis explores the distinct effects of maternal perinatal probiotic intake and obesity (induced by chronic consumption of a high fat diet [HFD]) on the behaviour, brain-gut metabolism, and neuroplasticity gene expression of the offspring. Maternal diet-induced obesity was hypothesised to increase anxiety and depressive-like behaviour in the young offspring. Long-lasting behavioural changes were also expected in adult offspring. Additionally, I predicted that perinatal probiotic exposure would attenuate these behavioural changes and lead to changes in neuroplasticity gene expression alongside an increase in faecal short-chain fatty acids acetate, butyrate, and propionate. It was then determined whether a serum metabolomic profile of depressive symptoms could be detected in the context of metabolic dysfunction in humans, whereby I expected to observe an additive effect of depression on serum markers of dyslipidaemia and inflammation in NAFLD. Methods: Female CD-1 mice were fed either a HFD or control diet for 6 weeks prior to mating until three weeks postpartum (PND21). At the time of conception through to PND21, a multispecies probiotic supplement (or vehicle control) was administered through the drinking water. At the time of weaning, dams and half the juvenile offspring were assessed for anxiety and depressive-like behaviours, and the faecal, liver, blood, and brain metabolome were quantified using nuclear magnetic resonance (NMR) spectroscopy. In the offspring prefrontal cortex, mRNA expression of genes relating to neuroplasticity, astrocyte metabolism, and inflammation were quantified. The remainder of the offspring were weaned onto regular chow and at 4-months age were profiled similarly to the juvenile offspring. In translational work, a human cohort with NAFLD where >90% of individuals were obese, serum NMR metabolite profiles were compared between patients with depressive symptoms in the last 12-months (n = 81), lifetime depression (n = 30) and no history of depressive symptoms (n = 107) using multivariate statistics. Results: Prolonged high-fat diet feeding reduced maternal gut SCFA abundance, increased markers of peripheral inflammation, and decreased the abundance of neuroactive metabolites in maternal milk during nursing. Both the juvenile and adult offspring of obese dams exhibited increased anxiety-like behaviour, which were prevented by perinatal probiotic exposure. Maternal probiotic treatment increased gut butyrate and brain lactate in the juvenile and adult offspring and increased the expression of prefrontal cortex PFKFB3, a marker of glycolytic metabolism in astrocytes. PFKFB3 expression correlated with the increase in gut butyrate in the juvenile and adult offspring. The resilience of juvenile and adult offspring to anxiety-like behaviour was most prominently associated with increased brain lactate abundance. Individuals with NAFLD and recent depressive symptoms, but not lifetime depression, had a distinct serum metabolomic profile compared to those with NAFLD without depression. This signature was found to be independent of age, sex, medication, and disease severity. Serum triglycerides, VLDL, isoleucine, and the inflammatory biomarker of glycoprotein acetylation were key metabolites increased in patients with recent depressive symptoms. Conclusions: Taken together, the data in this thesis demonstrate a clear relationship between maternal diet-induced obesity and emotional dysfunction in the offspring. I also indicate that the gut microbiome may act as a key modifiable (and therefore treatable) feature of the relationship between maternal obesity and offspring brain function and behaviour. Lastly, I found that depressive symptoms in humans with liver disease, independent of demographic factors and liver disease severity, are associated with altered circulating metabolite concentrations such as increased serum isoleucine, triglycerides, and glycoprotein acetylation.